Pengembangan Sistem Informasi Sales Force Automation dan Service Automation Pemesanan dan Penjualan Menggunakan Metode Rational Unified Process (Studi Pada Kantin FILKOM Universitas Brawijaya) - Helmy Danu Prameireza; Yusi Tyroni Mursityo; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
There are some problems that had been found in the current information system canteen Faculty of Computer Science (Filkom). These problems can affect customer's satisfaction, for instance the business process of food order takes a long time and the sellers are confused while delivering the order. Hence there is a need for developing a system which can overcome these problems. This study uses modules on the operational Customer Relationship Management (CRM) Sales force automation (SFA) and Service Automation (SA). Rational Unified Process (RUP) is a framework which will be used for developing the information system which has iterative and incremental techniques. RUP method has several phases, the first phase is inception phase, then elaboration phase, construction phase and ending with transition phase. The implementation of the system is mobile device-based with android platform and firebase as the database server. The results of black-box testing with 47 test-cases were succeeded, compatibility testing with 12 different devices using Test Lab was successfully executed and User Acceptance Testing (UAT) shows that the value of acceptance from the buyer is 85,92% and 82,86% on the side of the FILKOM canteen and time testing showed that the business process to-be faster 4 minutes 30 seconds than the as-is business process. From he results of these tests by implementing this information system can facilitate and speed up the order and sales of the FILKOM canteen.